EVALUATION OF POTENTIALLY HAZARDOUS CONTAMINANTS IN ANTI-VIRAL HERBAL PRODUCTS USED IN CLINICAL PRACTICE - Kazi, Sarfaraz; Bais, Sanjay (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The main objective of this research was to collect information for consumers and practitioners of marketed non-registered preparations. According to the World Health Organization (WHO) (1998), only arsenic, cadmium, and lead have maximum acceptable concentrations in starting materials of 1.0, 0.3, and 10 ppm, respectively. The allowable limits for toxic heavy metals in raw herbal medicines (ppm) according to the WHO (2007) are 0.5, 2 ppm for mercury and chromium. Methods: The use of an atomic absorption spectrophotometer was used to determine the buildup of heavy metals such as arsenic (As), chromium (Cr), lead (Pb), mercury (Hg), and cadmium (CD) in commercialized formulations in India. A total of ten samples of herbal formulations containing Swertia chirata, Triphala, Haridra, Daruharidra, Kantakari, Brhati, Karcura, Sunthi, Marica, and Pippali were selected for this research. Results: The results of this survey show that levels of heavy metals exceeding the limits allowed in unlicensed herbal preparations marketed have been found in the plant-based formulations studied. The herbal formulations coded AV1, AV2, AV7, and AV8 were found to be contaminated by arsenic (As) and in AV2, AV4, AV6, AV7, AV8, and AV9 were found to be contaminated by lead (Pb) levels. Herbal formulations coded AV1, AV2, AV3, AV4, AV6, AV7, AV8, and AV9 were found to be contaminated by mercury level and chromium level was AV1, AV2, AV3, AV4, AV5, AV6, AV7, AV8, AV9, and AV10. Conclusion: This work shows that the heavy metal content has been found in plant-based formulations. Because these formulations accumulate in the body, they can damage the delicate organs of the patient.